The microangiopathy of pregnancy (Hematology Meeting Reports, 2009)
Hypercoagulabilty occurs in uncomplicated pregnancies, beginning already during the first trimester of gestation. Fibrinogen and factor VIII levels show a progressive increase, accompanied during the second trimester by an increase in VWF levels, while factor XIII levels progressively decrease to 50% during the third trimester.1 This is consistent with increased in vivo thrombin generation and fibrin formation,2 leading to an increased antithrombin turnover.3 Protein S levels show major modifications, reaching 50% levels of normal at term.1 During pregnancy a condition of acquired protein C resistance is relatively common, due to the increase in factor VIII and V levels and, more important, to their increased state of activation.4,5 Global fibrinolytic activity is depressed until delivery, mainly due to increased levels of plasminogen activator inhibitors 1 and 2.1 Moderate thrombocytopenia occurs during the last stages of pregnancy and is mainly due to hemodilution.6